(untitled) - Rief, Sandra F. (San Francisco, CA, 1998)
Written by a nationally known educator with two decades of experience in working with ADD/ADHD students. For fast, reliable information about attention deficit disorder, parents and teachers need only to refer to The ADD/ADHD Checklist. This unique resource is packed with up-to-date facts, findings, and proven strategies and techniques for understanding and helping children and adolescents with attention deficit problems and hyperactivity-- all in a handy list format.
Keywords: Attention-deficit-disordered children,Attention-deficit-disordered children,Attention-deficit-disordered children,Chứng thiếu chú ý ở trẻ em,Chứng thiếu chú ý ở trẻ em,Chứng thiếu chú ý ở trẻ em; Popular works,Education,Behavior modification,Công việc phổ biến,Giáo dục,Sửa đổi hành vi